KOMPOSISI HYMENOPTERA PERMUKAAN TANAH DI DUA AGROEKOSISTEM DAN HUTAN DI KANAGARIAN SUNGAI DUO KECAMATAN PAUAH DUO KABUPATEN SOLOK SELATAN - Mariani, Yance - (STKIP PGRI Sumbar, 2014)
Role of Hymenoptera in nature can give positive effect and negative toward animals and human. Positive benefit is such as predator, describe organic ingredient, handle bug and also help pollination. Negative benefit is as destroyer of plant in field for fruit, leaves, branch and flower. Change of condition is between rubber agroecosystem and society coffee with forest that is not yet became rubber agroecosystem and coffee become agriculture area, plantation which often change action of ant to bug. The research is about Hymenoptera Composition of Ground Surface in Two Agroecosystem and Forest At Kenagarian Sungai Duo Kecamatan Pauah Duo Kabupaten Solok Selatan has purpose to know Hymenoptera composition of ground surface and how chemical-physic factor surface in two agroecosystem and forest. The research is about Hymenoptera Composition of Ground Surface in Two Agroecosystem and Forest At Kenagarian Sungai Duo Kecamatan Pauah Duo Kabupaten Solok Selatan have been done in February-april 2014. This research uses descriptive survey. Take of sampling in this research include from three stations like, station I of rubber plant, station II of coffee plant and station III of forest around rubber plant and coffee. Take of sampling is done with Pitfall Trap Method. Trap is used by bucket plastic which is 15 cm of diameter and 6 cm of high. To shunned entering rain water, so trap is give roof with 25 x 25 cm with high 15 cm from ground surface. Based on the research that have been done about Hymenoptera composition in two Agroecosystem and forest can be concluded that Hymenoptera composition in ground surface is founded 4 subfamily, 12 genus and individual sum 174. Genus is with density and high frequency alike Diacamma (23.55%) and (15.62%) that is higher compared other genus. Lower frequency is Leptogencys, Camponotus and Solenopsis alike (5.07%). Chemical-physic factor of environment takes sample in three station between 23-240C, pH ground is around 6.6-6.7, water ground is between 52-67%, and organic ground C is 4.6-7.3%.